New solenoporaceans from Upper Triassic (?Norian-Rhaetian) reef limestones in central Iran - Senowbari-Daryan, Baba (Array, 2008)
Summary: Two reef-building red algae of the family Solenoporaceae – Solenopora rectangulata n. sp. and Parachaetetes dizluensis n. sp. – are described from a ?Norian-Rhaetian section of the Nayband ormation exposed south of the town of Bagherabad, northeast of Esfahan, central Iran. These algae build reef structures or patches up to 17 m thick, either on their own or in association with other reef-building organisms including sponges, corals, etc. Such solenoporacean reef structures have not been described before, either from Iran or elsewhere in the world. Morphologically, both algae are easily distinguished by the different sizes of their thalli and particularly by their branching pattern